Responsible leadership and project citizenship behavior: A cross-level investigation - Yang, Yuxin; Huang, Jieying; Wu, Pingping; Zheng, Xujiang; Lin, Han; Ji, Shule (Frontiers in Psychology, 2022)
Project citizenship behavior has an important positive impact on project success. Researching how to promote project citizenship behavior is an important issue in project management. Based on social learning theory, social exchange theory, and social cognitive theory, this paper adopted the method of questionnaire survey and hierarchical linear model (HLM) to analyze the collected data based on the sample of Chinese construction enterprises and verified this hypothesis. The results show that responsible leadership has a significant positive effect on project citizenship behavior, that moral identity mediates this relationship, and that team moral sensitivity positively moderates this mediating effect. The findings of the study systematically and deeply reveal the intrinsic mechanism of the cross-level influence of responsible leadership on project citizenship behavior, and provide new enlightenment for the practice of project management.